Evaluasi Kelayakan Bisnis dan Inovasi Pemasaran pada Industri Telur Asin Brebes - Surono Surono; Sigit Djalu Purwoko (Universitas Muhammadiyah Palembang, 2025)
This study evaluates the business feasibility and marketing innovation strategies for the salted egg industry in Brebes, with a focus on product innovation, production processes, and financial viability. The object of this research is the salted egg production business in Brebes, which has become a regional culinary icon known for its unique taste and traditional production methods. The research aims to assess the potential for growth in the Brebes salted egg industry, identify the opportunities and challenges faced by producers, and provide strategic recommendations for expanding into both domestic and international markets. The methodology employed a combination of qualitative and quantitative approaches, including interviews with industry stakeholders, consumer surveys, and financial analysis. SWOT analysis was used to evaluate the internal strengths and weaknesses, as well as external opportunities and threats that could impact the business. Financial analysis methods such as Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Period (PP) were applied to evaluate investment viability and long-term profitability. The findings indicate that the Brebes salted egg industry shows strong potential for growth, with opportunities to expand through product innovation and improved marketing strategies. The research concludes that implementing innovations in product varieties, production efficiency, and marketing strategies will enhance the competitiveness of Brebes salted eggs in the global market, positioning it as a leading product in the international food industry.